2010
DOI: 10.1007/s00203-010-0626-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro antagonism and of in vivo immune modulation and protection against pathogenic experimental challenge of two probiotic strains of Bifidobacterium animalis var. lactis

Abstract: The aim of the present study was to compare the effect of intragastric administration with two strains of Bifidobacterium animalis subsp. lactis (Bifido A and Bifido B), in gnotobiotic and conventional mice, challenged with Salmonella Typhimurium. In vitro antagonism test showed that the two strains were able to produce antagonistic substances against various pathogenic microorganisms. In an ex vivo antagonism test the production of antagonistic substances was observed only against three out ten pathogens test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…In a recent clinical study, administration of probiotic lactic acid bacteria to patients with chronic periodontitis decreased the levels of IL‐1β in gingival crevicular fluid (GCF) 33 . Other studies also demonstrated that probiotic bacteria of the genus Bifidobacterium can increase levels of IL‐10 in non‐periodontal sites 34 , 35 . IL‐10 exerts inhibitory effects on IL‐1β and tumor necrosis factor‐alpha, which play synergistic roles in the inflammatory process, amplifying the host response 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent clinical study, administration of probiotic lactic acid bacteria to patients with chronic periodontitis decreased the levels of IL‐1β in gingival crevicular fluid (GCF) 33 . Other studies also demonstrated that probiotic bacteria of the genus Bifidobacterium can increase levels of IL‐10 in non‐periodontal sites 34 , 35 . IL‐10 exerts inhibitory effects on IL‐1β and tumor necrosis factor‐alpha, which play synergistic roles in the inflammatory process, amplifying the host response 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of IL-10 were also observed in colon of gnotobiotic mice challenged with Salmonella typhimurium and treated with B . lactis [26]. IL-10 is capable of inhibiting IL-1β and tumor necrosis factor-α, which present synergistic actions on inflammatory processes, amplifying the host response [27].…”
Section: Discussionmentioning
confidence: 99%
“…S. cerevisiae 905 induced a reduction in the levels of pro-inflammatory cytokines and modulated the activation of signaling pathways, such as the mitogen-activated protein kinase (p38 and JNK), NF-κB, and AP-1 pathways, which are involved in the transcriptional activation of pro-inflammatory mediators in the intestine (152). In addition, the probiotic treatment elevated the levels of secretory IgA in the intestine and of IgA and IgM in the serum and the production of the anti-inflammatory cytokine IL-10 in the intestine (153). Furthermore, Matins and collaborators demonstrated in vitro and in vivo that probiotic therapies could be useful as adjuvant when treating gastrointestinal diseases.…”
Section: Probiotics and Gut Immunitymentioning
confidence: 99%